Analisis Penanaman Nilai Karakter Religius Siswa Melalui Program Pembiasaan Membaca Surat-surat Pendek di SDN Pandeanlamper 04 Semarang - Arumsari, Rafika Yuli; S. Sumarno; Ismartiningsih; Siswanto, Joko (Jurnal Penelitian Multidisiplin Ilmu, 2024)
This study aims to analyze the implementation of the cultivation of students' religious character values through the habituation program of reading short letters at SDN Pandeanlamper 04 Semarang, as well as to identify the supporting and inhibiting factors in its implementation. This program is carried out every Thursday at 7.15-07.45 WIB which is attended by students from grade one to grade six students. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results show that this program is effective in improving students' understanding of religious values, such as faith, obedience, and noble character, as well as positive behavioral changes shown by students, such as discipline, tolerance, and responsibility. The main supporting factors include the active participation of teachers as role models and supervisors, as well as support from parents who reinforce learning at home. However, there are some inhibiting factors, including the lack of motivation of some students and the limited time for implementation at school.